재택근무와 직무만족 - 안종호 (The Graduate School, Ajou University, 2024)
2020년 초부터 시작된 코로나 팬데믹은 전 세계적으로 사회와 기업 환경에 극적인 변화를 가져왔다. 이러한 상황에서 많은 기업들이 비대면 업무 형태로 전환하면서 다수의 조직 구성원은 자기 의사와 관계없이, 재택근무라는 새로운 근무 형태를 경험하게 되었다. 그러나 재택근무가 조직 구성원들에게 미치는 영향에 대해서는 여전히 밝혀지지 않은 부분이 많다. 이에 본 연구는 기업에 근무하는 직원들이 재택근무를 통해 경험하는 직무만족도에 미치는 영향을 탐구하고자 하였다. 특히 개인 및 조직의 근무환경 특성이 재택근무와 직무만족 간의 관계에 어떠한 조절 효과를 가지는지를 상황적 요인으로 분석하여 재택근무가 조직 구성원의 직무만족에 미치는 다양한 요인들을 심층적으로 이해하고 향후 조직 운영 및 인적 자원 관리 전략 수립에 유용한 시사점을 제공하고자 한다. _x000D_ 본 연구는 우선 재택근무 관련 국내외 선행연구들에서 일관되게 지적되어 온 문제점, 즉 재택근무 및 이와 유사한 다양한 용어들의 개념과 정 의가 혼재되어 사용됨으로써 연구 과정과 결과에 혼선을 초래한다는 점에 주목하여 재택근무라는 연구 대상의 개념과 정의를 명확히 규정하는 것을 필수적인 사전 조치로 채택하였다. 이러한 기초적 접근을 바탕으로 본 연구는 재택근무 시 조직 구성원의 직무만족도를 향상시킬 수 있는 방법을 탐구한다. 이를 위해 성격 5요인과 같은 대표적인 개인 특성과 재택근무자의 근무지 장소와 시간에 대한 유연성 정도, 조직 내 커뮤니케이션 빈도, 직속상사의 리더십 스타일, 직무재량권 및 과업상호의존성과 같은 업무 특성들이 직무만족도에 미치는 조절효과를 분석한다. _x000D_ 본 연구는 국내 소재 중견기업 및 대기업에서 재택근무 경험이 있는 일반사무직 및 연구개발직 종사자 435명을 대상으로 온라인패널 설문 조사를 실시하여 통계분석에 사용하였다. 본 연구의 주효과 분석에서 독립변수인 재택근무의 정도와 직무만족도 사이에는 정(+)의 관계가 확인되었다. 이어진 위계적 다중회귀분석을 통해 조절변수의 영향을 조사한 결과, 개인의 성격 5요인 중에서 외향성이 직무만족도와의 긍정적 관계를 강화하는 유의한 조절효과를 나타내는 것으로 드러났다. 그러나 사전에 예측한 가설과는 달리 개방성, 성실성, 친화성, 신경증의 특성은 직무만족도와의 관계에서 통계적으로 유의미한 영향을 미치지 않았다. 재택근무자의 시간적 공간적 유연성은 직무만족도에 미치는 긍정적인 조절효과를 입증하였다. 이는 재택근무자들이 경험하는 시공간적 유연한 작업 환경이 직무만족도를 증진시키는 중요한 요인임을 시사한다. 더불어 본 연구는, 상사의 리더십 성향이 재택근무자의 직무만족도에 미치는 영향을 검토하였다. 연구 결과 임파워링 리더십 성향이 강한 상사의 경우 재택근무를 하는 부하직원의 직무만족도를 증진시키는 것으로 나타났다. 반면에, 지시적 리더십 성향이 높은 상사는 재택근무자의 직무만족도를 저하시키는 경향이 있었다. 이 효과는 통계적으로 표준 유의 수준인 p<.05에는 미치지 못했으나, 경계선상의 유의성을 나타내는 p=.059의 수준에서 관찰되었다. 그 밖에 직무재량권 역시 재택근무자의 직무만족도를 높이는 것으로 확인되었으며, 조직 내 커뮤니케이션 빈도 그리고 과업상호의존성은 통계적으로 유의하지 않게 결과가 나와 모두 기각되었다._x000D_ 본 연구 결과는 재택근무가 직무만족 향상에 유의미한 도움을 준다는 것을 확인함과 동시에, 이전 선행연구들에서는 미처 확인하지 못했던 재택근무자들의 성격과 같은 개인적 특성 및 재택 근무지의 시공간적 유연성, 상사의 리더십, 직무재량권 등과 같은 근무환경 특성의 중요성에 대한 새로운 통찰을 제공한다. 그리고 재택근무라는 새로운 근무 방식을 도입하는 기업들이 직원들에게 더 자율적이고 주도적으로 일할 수 있는 근무환경을 만들어 주는 것은 매우 중요하다는 점을 강조하고 있다. 또한, 향후 사무실 근무와 재택근무를 혼합해서 운영하는 하이브리드 근무 방식이 상당히 주목받을 것으로 예상됨에 따라 이를 위한 기업들의 인사조직 전략 수립에도 일정 부분 기여가 되기를 기대해 본다. _x000D_ 한편, 본 연구는 코로나19 팬데믹이라는 특수한 시기가 지속되던 2022년 말에 재택근무를 경험했던 사람들을 대상으로 단일 시점에서 연구 데이터가 수집되었다. 따라서 팬데믹 이전부터 제도적으로 잘 정비된 정책 아래 재택근무를 일상적으로 시행하고 있는 기업에 본 연구의 결과를 확대 적용하거나, 횡단적인 방식의 자료 수집으로 인한 변수 간의 인과관계에 한계점이 존재할 수도 있다.|The emergence of the COVID-19 pandemic in early 2020 instigated profound changes globally, significantly affecting societal and corporate dynamics. During this period, a myriad of organizations shifted to remote work modalities, leading to an involuntary transition for many employees to working from home (WFH). Despite the widespread adoption of WFH, its comprehensive impact on organizational members is not fully understood. This study investigates the influence of WFH on job satisfaction among employees in general corporations, specifically analyzing how individual and organizational work environment characteristics serve as moderating factors between WFH and job satisfaction. This research aims to enrich the understanding of factors affecting job satisfaction in WFH contexts and contribute insights for future organizational and human resource management strategies._x000D_ A notable issue identified in both domestic and international WFH literature is the confusion arising from the inconsistent use and ambiguous definitions of WFH and related terminologies. Addressing this, this study prioritizes establishing a clear definition and concept of WFH as an essential preliminary step. Based on this foundation, the study explores methods to enhance job satisfaction during WFH. It incorporates key personal characteristics, such as the Big Five personality traits, and evaluates the moderating effects of work environment characteristics, including WFH location and time flexibility, frequency of organizational communication, immediate supervisors' leadership styles, job discretion, and task interdependence. The proposed research model systematically encompasses these aspects._x000D_ The study employs statistical analysis on data collected via an online panel survey from 435 office and R&D employees with WFH experience from mid-sized and large corporations in South Korea. Initial analysis revealed a positive correlation between the extent of WFH and job satisfaction. Subsequent hierarchical multiple regression analysis demonstrated that Extraversion significantly enhanced the positive relationship with job satisfaction among the Big Five personality traits. However, other traits such as Openness, Conscientiousness, Agreeableness, and Neuroticism did not show significant effects on job satisfaction. The study confirmed that temporal and spatial flexibility in WFH positively moderates job satisfaction, highlighting the importance of a flexible working environment for telecommuters. Furthermore, the impact of supervisors' leadership styles was examined, indicating that empowering leadership boosts job satisfaction in a WFH setting, whereas directive leadership tends to decrease it. Although not reaching conventional levels of statistical significance (p<.05), this effect was observed at a borderline level of significance (p=.059). Job discretion was also found to positively influence job satisfaction, while the frequency of organizational communication and task interdependence showed no significant effects._x000D_ The findings validate that WFH can substantially enhance job satisfaction and offer new insights into the significance of personal characteristics like personality and work environment factors such as WFH flexibility, leadership, and job discretion. The study underscores the necessity for companies to create environments that support autonomy and initiative, especially considering the likely continuation of WFH and the rising trend of hybrid work models post-pandemic. These insights are expected to contribute to the formulation of relevant organizational and HR strategies._x000D_ However, the study's limitations stem from data collection focused on individuals who experienced WFH during the pandemic in late 2022. Caution should be exercised in generalizing these findings to companies with established WFH policies prior to the pandemic or interpreting causality from a cross-sectional data collection.
학위논문(박사)--경영학과,2024. 2
Keywords: 근무지 유연성; 성격 5요인; 임파워링 리더십; 재택근무; 직무재량권